Adsorbent derived from sugarcane bagasse and corn husk for potential ammonia gas removal - Guan, Billy Teck Huat (2013)
Agriculture wastes such as sugarcane bagasse (SB) and corn husk (CH) can be converted into low-cost adsorbents. The conversion of SB and CH into adsorbent will have two purposes. First, unwanted agricultural wastes are cheap, renewable, and abundant and thus can be converted into useful, added value adsorbents and second,the use of agricultural wastes as raw materials for making adsorbents can contribute in solving parts of the solid waste management and treatment problems in the country. The raw fibers were made into pellets of known composition (mixing ratios) of SB and CH. They were then converted into activated carbon through a physical activation method in which they undergo carbonization heat treatment at 800°C under nitrogen atmosphere, followed by activation in air for 40 minutes. For the first objective in this study, both the raw fiber and the activated carbon of SB and CH (SBCHAC) pellets were characterized for their physical and chemical properties in which they are performed by proximate analysis, ultimate analysis, surface pH, thermogravimetric analysis, porosity analysis, Fourier transform infrared spectroscopy, scanning electron microscopy, and energy dispersive X-ray. For the second objective, the adsorbents were assessed to determine their ability and potential to remove gaseous ammonia (NH₃) due to ubiquity in the environment and risk to human health. The study found that the activated carbon labeled SBCHAC4 with a Brunauer-Emmett-Teller surface area of 255.909 m² g‾¹ had the highest removal efficiency for NH₃, which is in overall slightly less superior to the commercial coconut kernel activated carbon. The results also show a statistically significant difference in the removal efficiency of NH₃ by SBCHAC4 between different NH₃ concentrations. The NH₃ adsorption by SBCHAC4 was found to follow the Langmuir and Freundlich isotherm model, and the adsorptive capacity of NH₃ for SBCHAC4 was 0.495 mg g‾¹. Finally for the third objective, the production yield of SBCHAC4 was determined and the production cost of SBCHAC4 was estimated to assess its affordability due to the fact that commercially available activated carbons are still expensive because of the use of non-renewable and relatively high-cost starting material. The activated carbon preparation for SBCHAC4 has resulted in 29.73% of yield. The studies indicate that SBCHAC4 could be listed as one of the most economical and effective adsorbent to be produced, which is justified in pollution control applications.